2019
DOI: 10.1021/acsbiomaterials.9b00603
|View full text |Cite
|
Sign up to set email alerts
|

Doped Graphene Quantum Dots for Intracellular Multicolor Imaging and Cancer Detection

Abstract: Despite significant advances of nanomedicine, the issues of biocompatibility, accumulation-derived toxicity, and the lack of sensing and in vivo imaging capabilities hamper the translation of most nanocarriers into clinic. To address this, we utilize nitrogen, boron/ nitrogen, and sulfur-doped graphene quantum dots (GQDs) as fully biocompatible multifunctional platforms allowing for multicolor visible/ near-IR imaging and cancer-sensing. These GQDs are scalably produced in one-step synthesis from a single bioc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
124
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(125 citation statements)
references
References 82 publications
(126 reference statements)
1
124
0
Order By: Relevance
“…In order to obtain GQDs with good biocompatibility, sensing and in vivo bioimaging capabilities, Campbell et al [111] used glucosamine-HCl solution as a carbon source and added different dopant precursors (sulfur thiourea or benezeneboronic acid) to synthesize various GQDs, including N-GQDs, NS-GQDs, and BN-GQDs. After the mixed solution was subjected to microwave treatment for 40 min, it was treated with dialysis membranes for 7 days, and GQDs with QY of 15-20% were obtained.…”
Section: Microwave Methodsmentioning
confidence: 99%
“…In order to obtain GQDs with good biocompatibility, sensing and in vivo bioimaging capabilities, Campbell et al [111] used glucosamine-HCl solution as a carbon source and added different dopant precursors (sulfur thiourea or benezeneboronic acid) to synthesize various GQDs, including N-GQDs, NS-GQDs, and BN-GQDs. After the mixed solution was subjected to microwave treatment for 40 min, it was treated with dialysis membranes for 7 days, and GQDs with QY of 15-20% were obtained.…”
Section: Microwave Methodsmentioning
confidence: 99%
“…Recently, visible lightemitted S-GQDs have also been used for cellular imaging (Jin et al, 2018). In contrast, Campbell et al reported multicolor emissive S-doped, N-doped, and B,N-co-doped GQDs for both visible and NIR-I imaging in vitro (Campbell et al, 2019). Under different excitation wavelengths, these doped GQDs emitted blue (450 nm), green (535 nm), and red (750 nm) light ( Figure 10A).…”
Section: Fluorescence Imagingmentioning
confidence: 99%
“…They can be utilized for drug/gene delivery while protecting their payload, targeting it to the tissue of interest, and tracing the delivery pathways via a plethora of bioimaging approaches. [1][2][3] As opposed to conventional fluorophores or MRI/CT agents, nanomaterials offer a large modifiable platform for covalent/non-covalent functionalization with biomolecules, [4] generally yield lower toxicity, [5][6][7][8] and offer an expanded and tunable emission spectral range. [9,10] Even though conventional fluorescence markers often have higher quantum yields, [11] the nanomaterial platforms are generally more photostable and, in the long run, provide more quantitative fluorescence tracking and assessment of payload bioavailability.…”
Section: Introductionmentioning
confidence: 99%
“…However, despite these advantages, the majority of nanomaterials are still restricted from large-scale in vivo applications by complex synthetic routes and high production costs, [17,18] size-dependent [19] /accumulation-derived toxicity, [20] as well as shallow-depth fluorescence imaging in the visible [21,22] suitable mainly for in vitro applications. Very few are biodegradable, [6] nontoxic, [23] or suitable for in vivo imaging or sensing applications [24] without the addition of toxic contrast agents, [25] while few-to-none combine all of these properties. In this work, we aim to generate and examine such multifunctional materials utilizing the capability of functionalized nanoscale systems for near-infrared fluorescence imaging underexplored in current bioimaging technologies due to scarcity of molecular fluorophores exhibiting radiative transitions in that region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation